Revenue Administration : Administering Revenues from Natural Resources - Lemgruber, Andrea (Washington, D.C. : International Monetary Fund, 2014)
Many developing countries have significant natural resource endowments, presenting a remarkable opportunity to boost long-term growth. However, this opportunity comes with enormous challenges. To maximize social and economic benefits, strong governance and institutional capacity are essential. Effective and transparent tax administration is crucial for properly managing revenues from natural resources so the country may benefit economically and socially from its natural resources. Revenue Administration describes the challenges that developing countries face and presents good practices to help build countries' long-term institutional capacity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet